Can wisdom guide intelligence and creativity toward prosocial ends? Evidence from humanistic, domain-aligned assessments - Zhang, Jingmin; Wang, Yuling; Tian, Liuqing (Intelligence (Norwood), 2026)
Wisdom is theorized to regulate the ethical use of cognitive strengths, but empirical evidence for its moderating role remains limited and inconsistent. This research investigates whether wisdom guides the application of intelligence and creativity toward prosocial ends, using domain-consistent, humanistic assessments across two studies (N = 933). Study 1 employed performance-based measures to examine how state-level wisdom influences the prosocial deployment of social intelligence and real-life creativity in morally complex scenarios. Study 2 used self-report measures to explore trait-level associations among integrative wisdom, social intelligence, creativity, and social mindfulness. Across both studies, wisdom consistently moderated the link between creativity and prosociality: higher wisdom predicted either stronger positive associations (Study 2) or buffered against ethically problematic use (Study 1). In contrast, no consistent evidence was found that wisdom similarly guided the use of intelligence. These findings suggest that wisdom functions as a selective moral regulator, more effectively shaping the ethical expression of open-ended, generative capacities such as creativity than of structured, instrumental capacities such as intelligence. The results underscore the importance of aligning constructs within shared evaluative domains and provide preliminary empirical support for wisdom as a meta-capacity that channels value-sensitive strengths toward socially constructive ends. •Wisdom selectively guided the ethical use of creativity, but not intelligence.•Creativity was more morally malleable than intelligence across two studies.•Wisdom protects against the misuse of creativity in moral dilemmas (Study 1).•Trait-level wisdom strengthens links between creativity and prosociality (Study 2).•Domain-aligned, humanistic assessments were used across both studies.